Single-dose Acute Oral Toxicity Study of Chloroform Extract of Snake Plant (Sansevieria trifasciata Prain.) Leaf in Wistar Rats (Rattus norvegicus Berkenhout, 1769) - Laksmindra Fitria; Isma Cahya Putri Gunawan; Wilda Bunga Tina Sanjaya; Maura Indria Meidianing (Universitas Gadjah Mada, 2022)
Sansevieria trifasciata is one of popular ornamental plants which also believed possessing therapeutic effects due to their phytochemical constituents. Secondary metabolites of plants can be toxic to other organisms; therefore, toxicity studies must be carried out to investigate adverse effects prior to further exploration as potent candidates of medicinal plants. This research aimed to evaluate toxicity and safety of consuming chloroform extract of S. trifasciata leaf (CESTL) in acute phase using female Wistar rats as model animal. Procedure referred to OECD Guidelines for the Testing of Chemicals, Test No. 420: Acute Oral Toxicity - Fixed Dose Procedure with single-dose administration of 2000 mg/kg bw. Results demonstrated that during 14 days of the experiment, neither mortality and sublethal effects as signs of toxicity were detected. There were no significant differences during the experiment between treatment groups and control in body weight, core temperature, individual and social behavior, food and water intake, as well as hematological profile, clinical biochemistry parameters, and relative organ weight (visceral organs indices). Almost all values were maintained within normal range (baseline) with fluctuation as normal physiological dynamics appeared relatively similar in all groups. Therefore, it can be concluded that no-observed-adverse-effect-level (NOAEL) for single-dose oral administration of CESTL with the dose 2000 mg/kg bw and can be classified in the hazard of Category 5 based on Globally Harmonized System of Classification and Labelling of Chemicals (GHS). Based on this finding, we will continue to conduct further study to assess the repeated-dose acute oral toxicity.